2017
DOI: 10.4317/jced.53602
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation: Oral leukoplakia surgical management using diode laser, CO2 laser, and cryosurgery

Abstract: BackgroundThe comparatively evaluate the three surgical treatment modalities namely cryosurgery, diode and CO2 laser surgery in terms of healing outcomes on the day of surgery, first and second week post operatively and recurrence at the end of 18 months was assessed.Material and MethodsThirty selected patients were divided randomly into three groups. Each group comprising of ten patients were subjected to one of the three modalities of treatment namely cryosurgery, diode laser or CO2 laser surgery for ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Several studies discussed the competencies of laser technologies for OLs, as the development of this technique is moving toward a painless and bloodless oral surgery. 2 3 4 Our work sustains this thesis and confirms CO 2 laser as a valid option for treatment of OLs as biopsy, vaporization, or removal.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Several studies discussed the competencies of laser technologies for OLs, as the development of this technique is moving toward a painless and bloodless oral surgery. 2 3 4 Our work sustains this thesis and confirms CO 2 laser as a valid option for treatment of OLs as biopsy, vaporization, or removal.…”
Section: Discussionsupporting
confidence: 72%
“…It has been recommended to treat benign OLs, such as fibromas, vascular anomalies, mucoceles, ranulae, gingival hyperplasias with different causes (idiopathic or due to side effects of medications), aphthous ulcers, mucosal frenula, or tongue ties (ankyloglossia), as well as premalignant lesions such as oral leukoplakia, erythroplakia, papillomas, and lichen planus. 4 5 6 7 8 Some reports on the use of the CO 2 laser also support the possibility of treating malignant oral diseases in early stages with excisional biopsies, as well as mucosal melanomas. 2 9…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…These effects are closely related to the laser settings (fibre, power, exposure time). The best results, in terms of healing, occur with a fluency of about 4 J/cm 2 [21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that all three surgical modalities used in this study were effective for treatment of OL, and the overall summation of the results of the study showed that laser therapy (CO 2 and diode) seems to offer better clinically significant results than cryotherapy. 16 It has been mentioned that diode laser with wavelengths ranging from 810 to 980 nm in a continuous or pulsed mode can be used as a possible method of soft tissue surgery in the oral cavity. 17,18 The major advantages mentioned in the literature for the use of CO 2 and diode lasers are minimal postoperative swelling and scarring, improved wound healing, and decreased postoperative pain and swelling due to transfer of high laser energy to the lesional site, resulting in minimal tissue damage.…”
Section: Ijaimsmentioning
confidence: 99%